The Effects of Performing Mental Exertion during Cycling Exercise on Fatigue Indices - Barzegarpoor, Hamidreza; Amoozi, Hamid; Rajabi, Hamid; Button, Duane; Fayazmilani, Rana (International Journal of Sports Medicine, 2020)
This study investigated the effect of performing prolonged mental exertion during submaximal cycling exercise on exercise tolerance and fatigue. Participants performed 5 experimental sessions. Session 1: determination of cycling peak power output. Sessions 2 and 3: cycling to exhaustion at 65% peak power output with mental exertion or watching a movie. Sessions 4 and 5: cycling for 45 min at 65% peak power output with mental exertion or while watching a movie. During sessions 2–5, rate of perceived exertion and heart rate were recorded while cycling and cortisol and prolactin concentrations, psychomotor vigilance task performance, and maximal voluntary contraction were measured pre-and post-sessions. During sessions 2 and 3, time to exhaustion was reduced (p<0.01) and rate of perceived exertion was increased (p<0.01) in session 2 compared to 3. Cortisol, prolactin and heart rate increased and psychomotor vigilance task and maximal voluntary contraction decreased from pre-to post-sessions with no difference between sessions. Cortisol, prolactin and rate of perceived exertion were higher (p<0.03) in session 4 than 5. Heart rate increased and maximal voluntary contraction decreased from pre-to post-sessions with no difference between sessions. Prolonged mental exertion during cycling exercise reduces exercise tolerance, which appears to be mediated psychologically rather than physiologically.
Keywords: mental fatigue; exercise tolerance; rating of perceived exertion; stress hormones